2019
DOI: 10.1088/1755-1315/313/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Assessment of Mount Merapi Eruption in Settlement Area of Sleman Regency

Abstract: Mount Merapi is one of the most active volcanoes in Indonesia. Seeing the status of Mount Merapi which until now is still quite active, disaster mitigation action efforts are needed. One of the disaster mitigation actions is by making the Risk Map. This study aims to provide an assessment of risk assessment of eruption of Mount Merapi in settlement areas so as to minimize losses that can occur. Mapping of eruption risk of Mount Merapi using two parameters, namely hazard and vulnerabilities. Risk assessment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…According to the hazard level of disaster-prone areas, Palemsari Hamlet is classified as KRB III with the highest hazard level (Fig. 1) [11]. In line with this data, Palemsari Hamlet was found to experience 100% land damage, including agricultural land, during the 2010 eruption.…”
Section: Resultssupporting
confidence: 52%
“…According to the hazard level of disaster-prone areas, Palemsari Hamlet is classified as KRB III with the highest hazard level (Fig. 1) [11]. In line with this data, Palemsari Hamlet was found to experience 100% land damage, including agricultural land, during the 2010 eruption.…”
Section: Resultssupporting
confidence: 52%
“…Their findings demonstrated that the factors of migrate-in population number and number of women had the greatest influence on social vulnerability. Meanwhile, Nugraha et al [17] conducted a risk assessment of Mount Merapi in the Sleman Regency habitation area, focusing on mapping eruption risk. The results showed that there is still a significant danger to this regency.…”
Section: Mount Merapi Evacuationmentioning
confidence: 99%
“…The study of Jumadi et al (2019) has several limitations such as the variability of population behavior that has not been involved in this initial simulation development, and the government contingency plans have not yet been considered. Meanwhile, Nugraha et al (2019) confirmed the risk assessment of Mount Merapi in the settlement area of Sleman Regency and concern on the mapping of eruption risk. The result shows that there is still a large risk in the Regency.…”
Section: Social Vulnerability Indexmentioning
confidence: 60%